Gender difference in association between low muscle mass and risk of non-alcoholic fatty liver disease among Chinese adults with visceral obesity - Lu, Yayun; Xia, Qing; Wu, Liangyu; Xie, Zhiping (Frontiers in Nutrition, 2023)
Background and Aims: Although the association between low muscle mass and the risk of non-alcoholic fatty liver disease is well-known, it has not been explored in viscerally obese populations by gender. Besides, whether low muscle mass still increases the NAFLD risk in subjects with visceral obesity, independent of obesity, is still unknown. The aim of this study was to explore the gender-specific association between low muscle mass and the risk of non-alcoholic fatty liver disease (NAFLD) in subjects with visceral obesity. Methods: Overall, 1114 participants aged 19-89 years were recruited in this retrospective study. Liver disease was diagnosed by hepatic ultrasound. Skeletal muscle mass was estimated by bioimpedance analysis and defined by the appendicular skeletal muscle index (ASMI). Gender- specific differences in the ASMI value were compared between NAFLD and control groups. Restricted cubic spline and multivariate logistic regression were performed to analyze the association (stratified by gender and age) between the ASMI and the risk of NAFLD, respectively. Results: Middle-aged females (40-60 years) and males (of any age) with NAFLD had a significantly lower ASMI compared with controls (P-value <0.05). An inverse linear association was found between the ASMI and risk of NAFLD (all P for non-linearity >0.05). Lower quartiles of the ASMI conferred independent risk of NAFLD compared to higher quartiles (all P for trend <0.001). Low muscle mass conferred a higher risk of NAFLD in middle-aged females (adjusted odds ratio=2.43, 95% confidence interval:1.19-4.95) and males (18-39 years: 3.76 [1.79-7.91]; 40-60 years: 4.50 [2.16-9.39]; and >60 years: 4.10 [1.13-14.84]). Besides, Low muscle mass and low muscle mass with obesity increase the risk of developing NAFLD, independent of obesity. Conclusion: Among those with visceral obesity, low muscle mass increased the risk of NAFLD in males of any age, and middle-aged females, this may be explained by the postmenopausal decline in estrogen.